2014
DOI: 10.1002/ange.201310905
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Anion Phase Transfer of Aryldiazonium Cations: An Enantioselective Synthesis of C3‐Diazenated Pyrroloindolines

Abstract: Herein is reported the first asymmetric utilization of aryldiazonium cations as a source of electrophilic nitrogen. This is achieved through a chiral anion phase-transfer pyrroloindolinization reaction that forms C3-diazenated pyrroloindolines from simple tryptamines and aryldiazonium tetrafluoroborates. The title compounds are obtained in up to 99% yield and 96% ee. The air-and water-tolerant reaction conditions accommodate electronic and steric diversity of the aryldiazonium electrophile and of the tryptamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In 2014, under the catalysis of chiral anion phase-transfer (CAPT), Toste and coworkers realized the CADA reaction of tryptamines 22 using aryldiazonium cations as a source of electrophilic nitrogen, which was in situ generated from aryldiazonium tetrafluoroborates 23 (Scheme 5). 14 By this approach, a series of C3-diazenated pyrroloindolines 24 were synthesized in overall high yields and excellent enantioselectivities. The authors suggested that the interaction of CPA (R)-C7 with aryldiazonium tetrafluoroborates 23 provided a soluble chiral ion pair, which controlled the enantioselectivity in the step of nucleophilic addition of tryptamines 22 to aryl-diazonium, thus generating an enantioenriched intermediate D to undergo the subsequent intramolecular cyclization to give products 24.…”
Section: Feng Shimentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, under the catalysis of chiral anion phase-transfer (CAPT), Toste and coworkers realized the CADA reaction of tryptamines 22 using aryldiazonium cations as a source of electrophilic nitrogen, which was in situ generated from aryldiazonium tetrafluoroborates 23 (Scheme 5). 14 By this approach, a series of C3-diazenated pyrroloindolines 24 were synthesized in overall high yields and excellent enantioselectivities. The authors suggested that the interaction of CPA (R)-C7 with aryldiazonium tetrafluoroborates 23 provided a soluble chiral ion pair, which controlled the enantioselectivity in the step of nucleophilic addition of tryptamines 22 to aryl-diazonium, thus generating an enantioenriched intermediate D to undergo the subsequent intramolecular cyclization to give products 24.…”
Section: Feng Shimentioning
confidence: 99%
“…13 Scheme 5 Organo-CADA reaction of tryptamines with aryldiazonium cations by Toste and coworkers. 14 reduced into N-Me groups by Red-Al, leading to the total synthesis of (−)-psychotriasine.…”
Section: Feng Shimentioning
confidence: 99%
“…Chiral phosphoric acids are versatile catalysts for many asymmetric reactions 8. In particular, many efficient strategies for asymmetric C3 functionalization of indoles and functionalization of enamines (enamides) by phosphoric acids have been well established 3a,g,j,k,o. 9 Herein we report a highly enantioselective [3+2] coupling of 3‐substituted indoles with quinone monoimines promoted by a chiral phosphoric acid.…”
Section: Screen Of the Chiral Phosphoric Acidsmentioning
confidence: 99%
“…[2] Among these transformations, dearomative annulation of indoles is the most straightforward method and has attracted much attention. [3] The benzofuroindoline core is a unique motif found in some important natural alkaloids, [4][5][6] such as diazonamides [4] and azonazine [5] (Figure 1). Since diazonamide A has been found to be a very potent anticancer agent owing to its high antitumor activity (IC50 < 5 nm), [4b,c] it has received considerable attention from chemists for the synthesis of these benzofuroindoline skeletons.…”
mentioning
confidence: 99%